1999
DOI: 10.1590/s0004-282x1999000600006
|View full text |Cite
|
Sign up to set email alerts
|

Panic disorder and hyperventilation

Abstract: -Respiratory abnormalities are associated with anxiety, particularly with panic attacks. Symptoms such as shortness of breath, "empty-head" feeling, dizziness, paresthesias and tachypnea have been described in the psychiatric and respiratory physiology related to panic disorder. Panic disorder patients exhibit both behaviorally and physiologically abnormal responses to respiratory challenges tests. Objective: We aim to observe the induction of panic attacks by hyperventilation in a group of panic disorder pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Several studies have investigated respiratory symptoms in PD patients [2], [31], [32], [33] and found that, during PA, respiratory complaints are common, such as dyspnea and tachypnea. Some specific respiratory tests aimed at inducing PA have been used, demonstrating that respiratory maneuvers, such as hyperventilation [34], carbon dioxide inhalation [35] and voluntary apnea [36], may increase anxiety in PD patients and thereby trigger a PA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated respiratory symptoms in PD patients [2], [31], [32], [33] and found that, during PA, respiratory complaints are common, such as dyspnea and tachypnea. Some specific respiratory tests aimed at inducing PA have been used, demonstrating that respiratory maneuvers, such as hyperventilation [34], carbon dioxide inhalation [35] and voluntary apnea [36], may increase anxiety in PD patients and thereby trigger a PA.…”
Section: Discussionmentioning
confidence: 99%
“…In a preliminary study (19) we observed the induction of panic attacks by hyperventilation in a group of panic disorder patients (DSM-IV). Thirteen panic disorder patients and 11 normal volunteers were randomly selected and induced to hyperventilate (30 Table 2 -Subjective anxiety levels rated by the subjects just before and after hyperventilation (mean ± SD).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperventilation provoked a PA in 3/12 PD subjects (25%) (Gorman et al, 1984), and in another study elicited mild fear in 20% of PD subjects (3/15), and no PAs (defined as moderate to strong fear response) (Antony et al, 1997). In other studies using a hyperventilation challenge, PD subjects had a PA (defined as 4 or more symptoms of a PA in the DSM-IV, with at least one cognitive fear symptom) response rate of 46% (6/13) and healthy controls 10% (1/10) in one study (Nardi et al, 1999), and PD response rates of 46% (16/35) compared to response rates of 7% (2/30) in healthy subjects in another study (Nardi et al, 2001). Specific physical symptoms were not reported, nor were objective autonomic and endocrine measures assessed.…”
Section: Section 4 – Panic Attacks Triggers: Laboratory and Potentialmentioning
confidence: 99%